2020
DOI: 10.21608/jhiph.2020.123383
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Risks of Female Hairdressers: Knowledge, Practice, and Self-Reported Symptoms

Abstract: Background & Objective(s): Hairdressers are exposed to various health hazards in their work environment. This study aims to assess the working conditions, knowledge, and practices regarding hazardous work exposure, in addition to identifying potential occupational health problems and their associated variables. Methods: A cross-sectional study including 151 female hairdressers was conducted in Assiut city, Upper Egypt. An interview questionnaire was used to record personal and job characteristics, descriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
2
Order By: Relevance
“…Regarding the organizational design of the hairdressing salons, the study showed that most hairdressers (68.5%) worked for 11 to 12 or more hours per day, with an average of 11 hours per day. This is different from other studies in the past (Khalaf et al,2021), where the average working hours is 8.9. The difference could result from a lack of compliance with labour regulations and the fact that the hairdressing occupation is informal, making the workforce work longer hours.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the organizational design of the hairdressing salons, the study showed that most hairdressers (68.5%) worked for 11 to 12 or more hours per day, with an average of 11 hours per day. This is different from other studies in the past (Khalaf et al,2021), where the average working hours is 8.9. The difference could result from a lack of compliance with labour regulations and the fact that the hairdressing occupation is informal, making the workforce work longer hours.…”
Section: Discussioncontrasting
confidence: 99%
“…The study's results revealed that 2.7% of salons had a higher temperature of 28-29˚C while most of the salons had a temperature range of 24-25˚C. The results were not comparable to other studies on the physical environment's effects on hairdressers' health (Khalaf et al, 2021). The discrepancy might be due to the weather conditions of the study areas.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…One study, out of the Netherlands, has found that hairdressers occupy a ‘close contact professional’ role and that workers in this category have been more likely to test positive to COVID-19 (de Gier et al, 2020). Prior to COVID-19, research already indicated the occupational health and safety risks of salons, including issues with hygiene practices and monitoring (Hepworth and Murtagh, 2005; Khalaf et al, 2020). Understandably, the pandemic heightens the importance of hygiene and raises issues around physical proximity for transmissibility of the virus between clients and workers.…”
Section: The Nature Of Salon Workmentioning
confidence: 99%